A novel amplitude and frequency demodulation algorithm for frequency-modulation atomic force microscope. (23rd August 2021) - Wang, Cheng; Li, Yingzi; Lin, Rui; Cheng, Peng; Xu, Zeyu; Qian, Jianqiang; Dou, Zhipeng; Wang, Jianhai; Li, Lei
Abstract: Frequency-modulation atomic force microscope (FM-AFM) has been a widely-used instrument to achieve atomic or subatomic resolution imaging. However, the low bandwidth of automatic gain control circuit for amplitude control loop and the low setting rate of frequency demodulation loop have been a big stumbling block for FM-AFM to realize fast measurement. In this article, a novel demodulation algorithm for FM-AFM is proposed. The Kalman filter approach is proposed to realize amplitude demodulation, and the FM signal is processed as a phase modulation signal (indirect FM signal). The performance of the algorithm is verified through experiment on field-programmable gate array, and compared with existing methods. Through the proposed method, the tracking performance of FM-AFM can be improved and the response rate can be increased without loss of precision.